A memory model for autonomous virtual humans - PETERS, CHRISTOPHER; O'SULLIVAN, CAROL ANN (My University, 2002)
A memory model based on ?stage theory?, the dominant view of memory from the field of cognitive psychology, is presented for application to autonomous virtual humans. The virtual human senses external stimuli through a synthetic vision system. The vision system incorporates multiple modes of vision in order to accommodate a perceptual attention approach. The memory model is used to store perceived and attended object data at different stages in a filtering process. The methods outlined in this paper have applications in any area where simulation-based agents are used: training, entertainment, ergonomics and military simulations to name but a few.
PUBLISHED
Keywords: ?stage theory? memory modelling; agent-object modelling